The significance of the hisbah's system in empowering the mosque's jurisdiction / Zanirah Mustafa @ Busu...[et al.] - Mustafa @ Busu, Zanirah; Aswad Ahmad, Mohd Miqdad; Nordin, Badriah (Universiti Teknologi MARA, Kedah, 2018)
In Islam, there is a requirement that needs to be completed by its followers known as Hisbah which means the calling of doing good deeds (amar ma'ruf, nahi munkar), and prohibiting forbidden deeds and fixing social breakdowns. Hisbah covers two responsibilities which are first, the responsibility to implement ma'ruf and secondly, the responsibility to stop the acts of munkar. These two responsibilities have been further divided into three categories which are responsibilities directly related to the rights of Allah SWT, responsibilities that are directly related to the rights of human beings and finally, the responsibilities related to the rights of Allah SWT and human beings. The purposes of these responsibilities are to deter any munkar related matters such as treachery, invasions, negligence, ruthless acts and similar conduct. Therefore, Islam has laid the foundations that need to be learned and understood by each individual in the matters of worship (ibadah) and human activities (muamalah). These matters need to be thoroughly learned through the basic foundation laid by the previous ulama and transformed with the new discoveries that are based on the principles of Islamic laws. There are various methods of hisbah that can be highlighted in the manners of hikmah, some examples are through the sharing of advice, tazkirah , irshad, qudwah, qiyadah, tawsiyyah and islah. The concept of hisbah is very relevant to be applied for welfare and justice especially in uniting the ummah and enhancing the understanding of Islam among the society. Therefore, the purpose of this study is to declare the relevance of the concept of hisbah to the current era especially in empowering the mosque as was practised during the golden age of Islam. The structure of the mosque's organization needs to be reevaluated to ensure that it is capable of performing its duty as one of the hisbah institutions in Malaysia.